Implementasi Wayang Kulit Sebagai Media Pembelajaran Agama Islam di SMKN 3 Banyumas Pada Era Masa Kini - Alatas, Muhyi Majid; Sudadi, Sudadi (IAINU Kebumen, 2025)
This study aims to examine the implementation of wayang kulit as a learning medium for Islamic Religious Education (PAI) at SMK Negeri 3 Banyumas. Based on preliminary observations, the use of wayang kulit in PAI learning at the school has, in fact, never been applied. The research employed a qualitative method with data collection techniques through interviews, observations, and documentation. The results indicate that the implementation of wayang kulit as a PAI learning medium is still at the trial stage and has not yet been carried out optimally. Supporting factors include the potential of Banyumas local wisdom, students’ interest in arts and creativity, support from art teachers and PAI teachers, as well as the availability of supporting facilities. Meanwhile, inhibiting factors involve the limited experience of PAI teachers in utilizing wayang kulit as a medium, limited planning time, management obstacles in the use of facilities, the media’s focus on certain students, and the lack of adequate infrastructure in general schools. This study concludes that local culture-based media such as wayang kulit hold great potential as an innovative medium for PAI learning while simultaneously preserving culture. However, it requires well-prepared planning strategies, teacher training, and sufficient facility support.